Application of Digital Methods in the Study of Ancient Travel - Laužikas, Rimvydas (Knygotyra, 2023)
The massive digitisation of written historical sources, optical character recognition (OCR) of texts, and their online availability in recent decades have created new opportunities and challenges for historical research. The digital humanities research model presented in this paper is based on the information organisation paradigm and the application of digital technology-based methods in studying ancient travels. The model has been developed and tested using the materials of the project “Homo Viator: Travel Space and Travellers’ Experiences in Early Modern Lithuania”. The main problem of the research is related to the fact that one of the essential sources of information about ancient travel are egodocuments (letters, diaries, memoirs, etc.) that contain journeys described alongside other important life events of a particular person. However, travel descriptions form only a small part of a text of a given egodocument and are unevenly distributed among different egodocuments. Therefore, given the size of the text of the egodocuments and their collections and the number of egodocuments published in different languages, researching them as sources in only one aspect (travel) requires a significant amount of human and time resources. A similar problematic situation exists with other sources of knowledge on ancient travel: a massive number of documents published in digital form (including OCR), their texts are voluminous, and the text fragments related to travel, country descriptions, ancient travel routes, travel and mobility infrastructure, and travellers’ experiences are relatively small and scattered throughout the source text. The research model described in the paper is divided into two steps: (i) collection of the corpus of OCR source texts; (ii) collection of empirical data using a dictionary-based computer-aided [or assisted] qualitative text analysis method implemented with the MaxQDA software. The collection of the source text corpus is carried out by applying the general principles and methods of online search of scientific publications. The corpus comprises authentic, published sources relevant to the study (letters, diaries, memoirs, etc.) and scholarly publications about them, thus forming two blocks of text - sources and literature. The literature block is used as additional material for a more precise selection and interpretation of the source texts. A key element for applying a dictionary-based computer-aided [or assisted] qualitative text analysis method is a high-quality dictionary that accurately describes the concepts (categories) relevant to the research. Considering the specificity of the sources (the languages used in the sources and their translations), a multilingual dictionary (Lithuanian-Polish-English-Russian-German) was compiled. The structure of the dictionary consists of six concepts (categories) related to ancient travel: (i) journey (general description), (ii) road and its infrastructure (bridges, fords, etc.), (iii) means of transportation, (iv) resting and accommodation places (towns, villages, taverns, post offices, etc.), (v) people encountered on the way (inn-keepers, highwaymen, guides, etc.), and (vi) food of the journey. A set of keywords and phrases describes each concept. In the last stage of the study, the research model was tested. The testing showed that the model could solve the above problems that arose during the project.